Melittin alcalase-hydrolysate: a novel chemically characterized multifunctional bioagent; antibacterial, anti-biofilm and anticancer - El-Didamony, Samia E.; Kalaba, Mohamed H.; Sharaf, Mohamed H.; El-Fakharany, Esmail M.; Osman, Ali; Sitohy, Mahmoud; Sitohy, Basel (Frontiers in Microbiology, 2024)
The prevalent life-threatening microbial and cancer diseases and lack of effective pharmaceutical therapies created the need for new molecules with antimicrobial and anticancer potential. Bee venom (BV) was collected from honeybee workers, and melittin (NM) was extracted from BV and analyzed by urea-polyacrylamide gel electrophoresis (urea-PAGE). The isolated melittin was hydrolyzed with alcalase into new bioactive peptides and evaluated for their antimicrobial and anticancer activity. Gel filtration chromatography fractionated melittin hydrolysate (HM) into three significant fractions (F1, F2, and F3), that were characterized by electrospray ionization mass spectrometry (ESI-MS) and evaluated for their antimicrobial, anti-biofilm, antitumor, and anti-migration activities. All the tested peptides showed antimicrobial and anti-biofilm activities against Gram-positive and Gram-negative bacteria. Melittin and its fractions significantly inhibited the proliferation of two types of cancer cells ). Yet, melittin and its fractions did not affect the viability of normal human lung Wi-38 cells. The IC50 and selectivity index data evidenced the superiority of melittin peptide fractions over intact melittin. Melittin enzymatic hydrolysate is a promising novel product with high potential as an antibacterial and anticancer agent.